Pengaruh Kemiskinan dan Pengangguran terhadap Pertumbuhan Ekonomi Wilayah Terpapar Tsunami 2004 (Studi Kasus Provinsi Aceh) - Wahyuningsih, Yayuk Eko; Putri Ansari, Leli; Jalil, Ivon (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research aims to analyze the impact of poverty and unemployment on economic growth in areas affected by the 2004 earthquake and tsunami, specifically in Aceh Province. The data used are secondary data sourced from the Central Bureau of Statistics (BPS) and the Regional Planning and Development Agency (Bappeda) of Aceh Province over a period of 19 years from 2005 to 2023. The method used is a quantitative method with a multiple linear regression analysis model. Based on the research results, it was found that poverty, measured by the percentage of the poor population, has a significant influence with a value of 0.074 at α = 10%. Meanwhile, unemployment measured by the open unemployment rate is not significant with a value of 0.234 at both α = 5% and α = 10%. The model equation is PE = 1.909 + 0.324PPM - 0.569TPT + ε. Next, the correlation coefficient value is 0.438 and the coefficient of determination is 9,0%.Meanwhile, the t-value is 0,090 for the coefficient of the percentage of poor population and -1.237 for the coefficient of the open unemployment rate, as well as the F-value of 1.895. Post-tsunami, starting in 2005, the percentage of poor residents continued to rise and began to decline after 6 years of the disaster, while the open unemployment rate also continued to increase in percentage and decreased 8 years after the tsunami. It is recommended to the local and provincial governments to launch poverty alleviation and unemployment reduction programs by creating job opportunities so that economic growth continues to increase in the future.